Energy Efficiency Maximization of Full-Duplex NOMA Systems With Improper Gaussian Signaling Under Imperfect Self-Interference Cancellation - Abu Mahady, Islam; Bedeer, Ebrahim; Ikki, Salama; Yanikomeroglu, Halim (IEEE communications letters, 2022)
This work addresses the energy efficiency maximization for a downlink cooperative full-duplex non-orthogonal multiple access (FD-NOMA) system in the presence of imperfect self-interference cancellation. We consider the case where users adopt improper Gaussian signaling (IGS) for their transmission and consequently derive the achievable rate of each link in the cooperative system. We jointly optimize the power allocation at the base-station and the IGS circularity coefficients of the cooperative IGS-based FD-NOMA system to maximize its energy efficiency subject to quality-of-service (QoS) requirements. Furthermore, improper constellation diagrams are designed using the predefined optimized IGS coefficients to study the impact of IGS on bit error rate performance. Simulation results demonstrate considerable energy efficiency performance gain of IGS-based FD-NOMA system over its proper Gaussian signaling (PGS)-based FD-NOMA counterpart under residual interference from imperfect self interference cancellation.